2020
DOI: 10.1167/iovs.61.3.49
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolic Characterization of Human Aqueous Humor in Relation to Wet Age-Related Macular Degeneration

Abstract: Purpose Energy compromise underpins wet age-related macular degeneration (wAMD) pathogenesis, but the relationship between glucose metabolism and the disease remains unclear. Here, we characterized aqueous humor (AH) to elucidate glucose-related metabolic signatures in patients with wAMD. Methods In total, 25 eyes of 25 patients with wAMD were divided into phakic (15 eyes), pseudophakic (10 eyes), and intravitreal injections of ranibizumab (13 eyes) wAMD groups. Twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…However, through excitotoxicity, it can result in neural cell damage or death, [34] which is thought to be mediated at least in part by oxidative stress [35]. Indeed, Charles-Messance et al [36] showed in a mouse model that glutamate alone is sufficient for inducing rod photoreceptor cell death and that this is due to the deregulation of glutamate homeostasis and glutamate excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, through excitotoxicity, it can result in neural cell damage or death, [34] which is thought to be mediated at least in part by oxidative stress [35]. Indeed, Charles-Messance et al [36] showed in a mouse model that glutamate alone is sufficient for inducing rod photoreceptor cell death and that this is due to the deregulation of glutamate homeostasis and glutamate excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical samples, higher levels of the intermediates of the TCA cycle were similarly detected in patients with active nAMD. In a previous study, using ultrahigh-performance liquid chromatography-tandem mass spectrometry, the detection of energy metabolites in the aqueous humor of with AMD revealed that citrate and isocitrate levels were significantly increased in the AMD group, whereas succinate and α-ketoglutarate levels were significantly decreased compared with the control group ( 106 ). Low α-ketoglutarate levels contribute to the stabilization of HIF-1α and the secretion of VEGF-A, which further promotes progression to CNV ( 107 ).…”
Section: Glucose Metabolism In Pathological Ocular Angiogenesismentioning
confidence: 98%
“…Thus, the dysregulation of the TCA cycle may also be a driving force in nAMD. However, the underlying mechanisms require further investigation ( 106 ).…”
Section: Glucose Metabolism In Pathological Ocular Angiogenesismentioning
confidence: 99%
“…Dysregulated lipid and glucose energy metabolism was speculated to be the driven force for wet AMD [ 83 ]. Hence, researchers conducted a targeted metabolomics study on the glucose metabolism and an untargeted metabolomics study [ 29 , 30 ]. The prior study analyzed the AH samples of 25 AMD patients and 25 controls via LC–MS [ 29 ].…”
Section: Application Of Metabolomics In Ocular Diseasesmentioning
confidence: 99%